Developing KAED Resource Centre database - Yaali, Syarel Azill; Ayob, Mohd Fairullazi (2018)
•The project is proposed to develop an online database record in the present KAED website to improve the visibility of theses, articles, dissertations, etc. that belong to KAED's academics, PG and UG students. •All data that to be kept are of the last 5 years (proposed) •The data are to be segregated by Departments and by year •For all materials, abstract is to be used as an introduction for the potential readers to know what is the thesis is all about